Herrera y Cervantes frente al mito de Ícaro en la poesía cancioneril: (dos notas sobre la poética herreriana y un contrapunto cervantino) - Trabado Cabado, José Manuel (Estudios Humanísticos. Filología, 1996)
The aim of this paper is the study of the device used by Herrera in order to introduce the myth of Icarus within the usual verse pattems of the cancioneril tradition, in which the use of mythology is most uncommon. To make this introduction possible, Herrera deftly manipulates several elements of XV century poetry such as boldness, fire, death, the lover identified with light, etc., which, added to the experience of Italian Petrarchists, allow him to make a series of allusions to the myth of the bold young, man. With this, we try to show a link between the poetry of Italian influence and the Castilian poetic tradition. Finally, the comparison of Herrera’s texts with a poem from La Galatea provides a meaningful epilogue for a contrast of attitudes and procedures